2022
DOI: 10.3390/plants11233285
|View full text |Cite
|
Sign up to set email alerts
|

Development of Two-Dimensional Model of Photosynthesis in Plant Leaves and Analysis of Induction of Spatial Heterogeneity of CO2 Assimilation Rate under Action of Excess Light and Drought

Abstract: Photosynthesis is a key process in plants that can be strongly affected by the actions of environmental stressors. The stressor-induced photosynthetic responses are based on numerous and interacted processes that can restrict their experimental investigation. The development of mathematical models of photosynthetic processes is an important way of investigating these responses. Our work was devoted to the development of a two-dimensional model of photosynthesis in plant leaves that was based on the Farquhar–vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 99 publications
5
21
0
Order By: Relevance
“…It was shown that the CO 2 assimilation rate and its coefficient of variation (CV(A hv )) were increased with increasing photosynthetically active radiation (PAR). The light saturation of these parameters was observed under illumination intensities equal to 500 µmol m −2 s −1 and more; this value was similar to the light saturation of A hv in pea leaves [42]. It should be noted that the CO 2 assimilation rate was more in the variant with stomata localized in center of a 3 × 3 cell square than in the variant with stomata localized in center of a 5 × 5 cell square (Figure 2a).…”
Section: The Influence Of Light Intensity and H + -Atpase Activity On...supporting
confidence: 77%
See 4 more Smart Citations
“…It was shown that the CO 2 assimilation rate and its coefficient of variation (CV(A hv )) were increased with increasing photosynthetically active radiation (PAR). The light saturation of these parameters was observed under illumination intensities equal to 500 µmol m −2 s −1 and more; this value was similar to the light saturation of A hv in pea leaves [42]. It should be noted that the CO 2 assimilation rate was more in the variant with stomata localized in center of a 3 × 3 cell square than in the variant with stomata localized in center of a 5 × 5 cell square (Figure 2a).…”
Section: The Influence Of Light Intensity and H + -Atpase Activity On...supporting
confidence: 77%
“…In accordance with our previous work [42], influence of light intensity on the photosynthetic CO 2 assimilation rate and on its spatial heterogeneity on the leaf surface was investigated at the first stage of the current analysis. Light dependence of the CO 2 assimilation rate and the variation coefficient of this assimilation are shown in Figure 2.…”
Section: The Influence Of Light Intensity and H + -Atpase Activity On...mentioning
confidence: 78%
See 3 more Smart Citations